Live-Work Housing Concept for Rusunawa in Indonesia: Is it Possible? - Vina Triyuliana; Susinety Prakoso (The Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
Living and working in the same unit is part of the everyday life of low-income people who live in slum areas to overcome their economic situation. However, when they are evicted from slums and relocated to Rusunawa (vertical public rental housing), their live-work life is no longer possible. Empirically, living in Rusunawa puts many residents in financial difficulties. This article is aimed to investigate the feasibility of a live-work housing concept for Rusunawa. Based on observations at Rusunawa Pesakih in West Jakarta, this article revealed that only 48% of a total of 64 commercial spaces provided by Rusunawa were occupied for home industry businesses. In-depth interviews with 40 residents showed that 70% of them had a diversity of potential skills related to home industries. However, their skills were unchanneled and unaccommodated. This article also found that 35% of them did take-home work-related activities in the corridors of Rusunawa. The findings indicated that there is a potential for live-work life in Rusunawa and an opportunity to bring back the live-work life into Rusunawa. This article proposes design recommendations for live-work housing concepts for Rusunawa by increasing the percentage of workplace units from 10% to 25% and by categorizing the Rusunawa units into four types according to the characteristics of the home industry: the regular type (36 m2), the live-with type (40 m2), the live-near type (40-54 m2), and the live-nearby type (60-70 m2). This article may provide inspiration for policymakers and architectural designers for future planning and design of Rusunawa that empower residents economically.Abstrak. Tinggal dan bekerja di unit yang sama adalah bagian dari kehidupan sehari-hari orang-orang berpenghasilan rendah yang tinggal di daerah kumuh untuk mengatasi situasi ekonomi mereka. Namun, ketika mereka diusir dari permukiman kumuh dan dipindahkan ke Rusunawa, lapangan kerja mereka hilang. Secara empiris, tinggal di Rusunawa menyebabkan kesulitan keuangan warga. Artikel ini bertujuan untuk menyelidiki kemungkinan konsep perumahan live-work untuk Rusunawa. Berdasarkan pengamatan di Rusunawa Pesakih di Jakarta Barat, artikel ini menemukan bahwa hanya 48% dari total 64 ruang komersial yang disediakan oleh Rusunawa ditempati untuk bisnis industri rumahan. Wawancara mendalam dengan 40 penduduk menunjukkan bahwa 70% dari mereka memiliki keterampilan keragaman potensial yang terkait dengan industri rumah tangga. Namun, keterampilan mereka tidak tersalurkan dan tidak diakomodasi. Artikel ini juga menemukan bahwa 35% dari mereka melakukan kegiatan yang terkait dengan pekerjaan di rumah di koridor Rusunawa. Temuan ini mengungkapkan bahwa ada potensi kehidupan live-work di Rusunawa dan kesempatan untuk membawa kembali kehidupan live-workke Rusunawa. Artikel ini mengusulkan rekomendasi desain konsep perumahan live-workuntuk Rusunawa dengan meningkatkan persentase unit tempat kerja dari 10% menjadi 25% dan dengan mengelompokkan unit Rusunawa menjadi empat jenis sesuai dengan karakteristik industri rumah. Mereka adalah tipe reguler (36 m2), tipe live-with (40 m2), tipe live-near (40-54 m2) dan tipe live-nearby (60-70 m2). Artikel ini dapat memberikan inspirasi bagi pembuat kebijakan dan perancang perumahan untuk perencanaan dan desain Rusunawa di masa depan yang dapat memberdayakan penghuninya secara ekonomis.Kata kunci. Desain perumahan publik, Rusunawa, perumahan berpenghasilan rendah, konsep live-work.